Teaching Critical Thinking and Argumentation In Education: An Evidence-Informed Design Framework for Instruction, Assessment and Equity - Bernardo Castillo Reyes Bernardo Castillo Reyes; Lucía Vargas Mendoza Lucía Vargas Mendoza (Kalam Practica Media, 2025)
Critical thinking and argumentation are among the most widely endorsed outcomes of contemporary education across virtually every national curriculum framework, professional accreditation standard, and employer capability profile, yet the gap between their rhetorical prominence and their genuine, systematic development in classroom practice remains stubbornly wide. Constructs are routinely invoked without the definitional precision that would make them teachable; instructional sequences are designed without the progressive scaffolding that reasoning development requires; and assessment systems rely on surface-level proxies that conflate engagement activity with reasoning quality. This evidence-informed conceptual paper synthesizes scholarship on critical thinking definitions and subject specificity, research on argumentation as a core dialogic and epistemic practice, and empirical syntheses of instructional approaches including meta-analyses of explicit reasoning strategy instruction, argumentation-based learning, problem-based learning, and writing-to-learn routines, to propose a practical, integrated design framework for teaching and assessing critical thinking and argumentation at scale. The framework articulates four interdependent domains: (a) construct clarity and disciplinary epistemic practices that specify observable reasoning moves calibrated to domain-specific standards of evidence and justification; (b) instructional routines for reasoning, dialogue, and inquiry that make argumentation a learnable, repeatable practice rather than an occasional activity; (c) formative assessment, feedback, and moderation routines that produce trustworthy, equitable judgments of reasoning quality; and (d) equity-by-design and accessibility supports aligned with Universal Design for Learning principles that ensure reasoning opportunities and participation structures are genuinely inclusive. Three tables present empirical data on instructional effect sizes across pedagogical approaches, rubric dimension performance distributions across student populations, and implementation quality benchmarks with associated outcome data. The paper concludes with actionable guidance for educators, instructional designers, and institutional leaders seeking to move beyond aspirational rhetoric toward coherent, evidence-grounded systems for developing and assessing critical thinking and argumentation as genuine educational outcomes.